Angiomatoid fibrous histiocytoma with EWSR1-CREB1 gene fusion occurs in lungs and ribs with systemic multiple metastases: a case report and review of the literature - Feng, Dongmei; Li, Ying; Li, Zhengjin; Pan, Yun; Gao, Yixuan; Cha, Jinyan; Zhang, Chunmei (Frontiers in Oncology, 2025)
Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor with intermediate malignant potential, and it rarely metastasizes. We encountered a unique AFH case where, the tumor was discovered initially in unusual locations—the left lung and the left 4th rib. Combined histological features with FISH and NGS analysis, the diagnosis of AFH was supported, however, it is difficult to determine which of these two is the primary lesion. Eight months after the initial surgery, multiple systemic metastases were detected, eventually leading to the patient’s death 18 months later due to widespread metastasis. Our case signifies the first reported occurrence of systemic metastasis in either bone-originating or pulmonary-originating AFH, and it is the initial instance of mortality resulting from multifocal metastasis originating from an atypical site.